Pengaruh Transparansi Kontrak, Insentif, dan Re-Employment Expectation (REE) terhadap Komitmen Kerja Tenaga Outsourcing pada Industri Brand Activation: di PT Pradipta Adhi Cipta - Linda Dwi Rafika; Bisma Jatmika Tisnasasmita; Natalia Christiani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
The increasing use of outsourcing labor in Indonesia, particularly in the brand activation industry, has raised concerns regarding work commitment among outsourcing employees due to issues related to contract clarity, incentives, and future employment opportunities. This study aims to examine the effects of contract transparency, incentives, and re-employment expectation (REE) on the work commitment of outsourcing employees at PT Pradipta Adhi Cipta. The study employed a quantitative approach with an explanatory research design. Data were collected through online questionnaires distributed to outsourcing employees who had participated in brand activation programs during the 2025–2026 period. A total of 255 valid responses were analyzed using multiple linearregression with SPSS. The analysis included validity, reliability, classical assumption tests, t-test, F-test, and coefficient of determination (R2). The results indicate that contract transparency, incentives, and re-employment expectation have positive and significant effects on employee work commitment, both partially and simultaneously. These findings suggest that contract clarity, appropriate incentives, and future employment opportunities play important roles in strengthening the work commitment of outsourcing employees in project-based work environments.